Sarcopenia Definition Outcome Consortium – defined Weakness and Risk of Falls: The National Health and Aging Trends Survey - Batsis, John A.; Haudenschild, Christian; Crow, Rebecca S.; Gilliam, Meredith; Mackenzie, Todd A. (Geriatrics & gerontology international, 2023)
Aim The prevalence of obesity continues to rise, as does that of weakness. However, it is unclear how this impacts the risk of falling. We aimed to ascertain the risk of falls using new definitions of clinically defined weakness. Methods We applied clinically defined weakness definitions to the National Health and Aging Trends Survey using the Sarcopenia Definitions Outcomes Consortium cutpoints. Three exposure variables were created: grip‐strength‐defined weakness and body mass index [GS/BMI]‐defined obesity; weakness and obesity, weakness and waist circumference‐derived obesity (GS/WC); and weakness defined by a ratio of GS÷BMI. Proportional hazards modeled incident falls as a function of weakness with/without obesity (hazard ratio [HR] [95% confidence intervals]). Results Of 4906 respondents aged ≥ 65 years (54.5% female), the mean ± SD grip strength, BMI, and WC were 26.7 ± 10.6 kg, 27.4 ± 5.4 kg/m2, and 99.5 ± 16.3 cm, respectively. Using the neither weakness/obesity as the referent, weakness was associated with incident falls across all definitions (GS/BMI: HR 1.19 [1.07, 1.33]; GS/WC: HR 1.39 [1.19, 1.62]; GS ÷ BMI: HR 1.16 [1.05, 1.28]). Weakness with obesity was associated with falls using GS/WC (HR 1.28 [1.11, 1.48]). Obesity status was associated with falls in both the BMI and the WC definition (1.17 [1.02–1.35], 1.16 [1.05–1.28]). Conclusion Our findings further evaluate the definitions of clinically defined weakness with and without obesity in older adults. As falls are an important patient outcome, establishing this relationship is critical for both clinicians and researchers. Future study should identify high‐risk individuals in order to direct specific interventions to them. Geriatr Gerontol Int 2023; 23: 213–220. We applied three of the Sarcopenia Definitions Outcomes Consortium definitions for clinically defined weakness to the National Health and Aging Trends Survey. Of 4906 respondents aged ≥ 65 years (54.5% female), using the neither weakness/obesity as the referent, weakness was associated with incident falls across all definitions (Grip Strength ÷ Body mass index: HR 1.19 [1.07, 1.33]; Grip Strength ÷ Waist Circumference: HR 1.39 [1.19, 1.62]; Grip Strength ÷ BMI: HR 1.16 [1.05, 1.28]). Findings further evaluate the definitions of clinically defined weakness with and without obesity in older adults.